Perancangan dan Implementasi Topologi WAN Menggunakan Routing Dynamic BGP Antar Cabang di PT Bank Woori Saudara Tbk - Ayub Amarrulloh; Sidik Sidik (Evolusi : Jurnal Sains dan Manajemen, 2022)
Technology in the form of a network system is one of the needs that must exist in every company because a large company must have a number of branch offices that are quite far away. especially between the head office which is located far from the branch office with the computer network system making it easier for companies to exchange information effectively and efficiently. One way to support this is by using the internet. However, to connect them there are rules that apply so that the networks communicate with each other, so certain techniques are needed, using wide area network (WAN) network technology. This study aims to facilitate the exchange of data and information communication lines between the Head Office and Branch Offices by designing and implementing a WAN topology, the author will use the concept of BGP Dynamic Routing Between Branches at PT. Bank Woori Saudara Tbk. The results of this study using BGP Routing (Border Gateway Protocol) there is an AS (Autonomous System) number assigned to each router. This AS serves as the identity of the router and router administration in recognizing the path of the neighboring router (neighboor) is active or not. In addition, by adding 1 (one) ISP at the head office of PT. Bank Woori Saudara Indonesia 1906 Tbk, can guarantee that the connection between the head office and branch offices remains connected. Finally, by using Dynamic Routing BGP fail-over can run well, with the dynamic routing work system being able to recognize whether the neighboring network is active or not. If it recognizes that the neighboring network is not active, the router will look for another alternative path.